Challenges in environmental ethics - Rolston, Holmes, 1932-2025, author; Prentice-Hall, publisher (Colorado State University. Libraries, 1998)
Environmental ethics is an invitation to moral development. Respect for human life is only a subset of respect for all life. What ethics is about is seeing outside your own sector of self-interest, of class interest. A comprehensive ethic will find values in and duties to the natural world. The vitality of ethics depends on our knowing what is really vital, and there will be found the intersection of value and duty. An ecological conscience requires an unprecedented mix of science and conscience, of biology and ethics.
Keywords: ecosystems; value theory; nature; science; culture; humans; environmental ethics; ecological conscience; organisms; species